(untitled) (Bangladesh Journal of Otorhinolaryngology, 2014)
Carcinoma Larynx is very rare in children and adolescents. Only few cases of childhood and adoloscent Carcinoma Larynx has reported worldwide. Exact cause of childhood and adoloscent Carcinoma Larynx is not known but few risk factors have been detected. Childhood and adolescent carcinoma Larynx is diagnosed delayed and its outcome is usually fatal. Earlier suspicion, accurate diagnosis and prompt intervention are essentially recommended. DOI: http://dx.doi.org/10.3329/bjo.v19i2.17636 Bangladesh J Otorhinolaryngol 2013; 19(2): 124-129